Consumer supply-chain demands and challenges at farmers' markets. Issue 12 (3rd December 2018) - Garner, Benjamin; Ayala, Cesar
Abstract : Purpose: The purpose of this paper is to examine consumer demands for local foods at a farmers' market. This includes examining both what products consumers want more of at the market and also what factors influence consumers' attendance for a weekday farmers' market. Design/methodology/approach: This study was based on open-ended comments from a market survey of 270 participants in a farmers' market in the USA. Findings: This study revealed that consumers want more products at the farmers' market that require significant resources and time to grow, such as meat and fruit. Consumers reported that they would be more likely to attend a weekday market if it had better hours of operation and better selection. Consumer comments also revealed that consumers often perceive the market to run out of products and not have the full supply that they want to purchase. Research limitations/implications: This research represents qualitative insights at one farmers' market in the USA. While there are observations that may transfer to other markets, caution should be used when generalizing these findings. Practical implications: This research is informative for farmers in providing them a list of consumer demands and also highlights the ways farmers need to make their market convenient to consumer work and life patterns. Originality/value: This work adds value to the literature by expanding our understanding of specific foods customers see as limited in the farmers' market, and it also provides much needed information regarding consumer behavior and weekday market attendance, which is not discussed as often in the literature.